The gap between desired and expected fertility among women in Iran: A case study of Tehran city. - Maryam Hosseini (Public Library of Science (PLoS), 2021)
The 2016 Iranian Census reveals that 14 of the country's 31 provinces have sub-replacement fertility. The province of Tehran, where a woman on average gives birth to 1.5 children during her reproductive period, has the lowest fertility in Iran. However, the 'two-child' norm prevails in the country and even a woman of young reproductive age still values having at least two children on average. In other words, there exists a gap between a woman's actual and desired fertility. This paper examines the demographic and socio-economic factors influencing the gap between actual and desired fertility in Tehran city based on a sample survey of 400 married women aged 15-49 years, conducted in 2015. The findings of the study reveal that the women of Tehran would be able to meet their fertility desires of two or more children if they were able to achieve their intended number of children they stated in the survey. However, should these women face any socio-economic constraint, they would be very likely to restrain their fertility desires and have fewer additional children than they initially intended, and thus continue with the sub-replacement fertility as being observed in Iran today.